Differences in ACTN3, ACE, and ADBR3 polymorphisms between Croatian National Team and non-national team elite soccer players - Lana Ruzic; Ivan Radman; Branka R. Matkovic (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2023)
Introduction: This study investigated the differences in ACTN3, ACE and ADRB3 variants in top-level soccer players who entered the Croatian National Team and the ones who did not but played for two best Croatian teams. Material and Methods: The buccal swabs were collected from 56 soccer players playing for the Croatian National Team (N = 31) and/or for one of the two most prestigious Croatian soccer clubs (N = 25). Each participant's genotype was determined by analyzing the single-nucleotide polymorphism. The ACTN3 gene (rs1815739) on chromosome 11 and the ACE (rs1799752) gene on chromosome 17 were determined. Results: No significant differences between the players who entered the national team and the ones who did not were found in ACTN3 R577X (p = 0.437) and ADRB3 (p = 0.202) polymorphism distribution, while the differences existed in ACE (p = 0.044). The significant differences were determined in the "Athletic index" between the national-team and non-national-team players (p = 0.023). Regarding the position, the "Athletic index" was significantly higher only in national team midfielders (2.50 ±1.08 points vs. 1.38 ±1.06; p = 0.034). Conclusion: It seems that the soccer players with a favorable genetic combination on the ACTN3 gene and ACE gene might have had a better chance to enter the National Team.